PENERAPAN MODEL GUIDED NOTE TAKING KOMBINASI EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN PENGUASAAN KONSEP MATERI GERAK LURUS - Cholis, Nur (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
Mastery of the concept of straight motion of students is still not optimal. Therefore, there is a need for a solution to overcome this problem. The purpose of this study is to describe the improvement of learning outcomes and the improvement of student learning activities on the material of straight motion through the guided note taking model combined with everyone is a teacher here. The type of research in this research is classroom action research. The subjects in this study were all students of X-MIPA 1 SMA Negeri 6 Semarang. Data collection techniques through tests and non-tests and data analysis techniques using descriptive analysis. The results of the study showed that the guided note taking learning model combined with everyone is a teacher here in the straight motion material for physics subjects was able to improve student learning outcomes, the percentage of classical completeness in cycle 2 was 83.33% compared to cycle 1 of 55.57%. Meanwhile, the guided note taking learning model combined with everyone is a teacher here is able to increase student learning activities according to the aspects of the activities observed during the learning process.